PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI PUSKESMAS PONDOK BETUNG TANGERANG SELATAN - Muhammad Andrean Syah H; Yusuf Supardi (SINERGI : Jurnal Riset Ilmiah, 2026)
Productivity is the process by which employees can produce performance that can be assessed as good or bad based on the results. This study aims to analyze the influence of motivation and work discipline on employee productivity. This research was conducted at the Pondok Betung Community Health Center in South Tangerang. The research sample consisted of 45 people, using a non-probability sampling technique. The method used in this study was a quantitative method. Equipped with a data analysis process using linear regression processed through SPSS 31. Based on the results of the tests that have been carried out by researchers, it is produced that motivation has a significant effect on work productivity with a significance value of 0.001 which indicates that the value is smaller than 0.05 (0.001 <0.05) and a calculated t value of 3.433, work discipline has a significant effect on work productivity with a significance value of 0.001 which indicates that the value is smaller than 0.05 (0.001 <0.05) and a calculated t value of 5.427, and motivation and work discipline together have an effect on work productivity with a significance value of 0.001. By using a significance level of 0.05, the F significance value of 0.001 indicates <0.05. Then the calculated F value of 70,784 is obtained. The coefficient of determination (Adjusted R Square) is 0.771, or 77.1%. This means that 77.1% of the variation in employee productivity (Y) can be explained by motivation (X1) and work discipline (X2), while the remaining 22.9% is influenced by other factors not included in this model. The regression analysis clearly shows that motivation and work discipline are important factors that significantly and positively impact employee productivity at Pondok Betung Health Center, both individually and collectively